Familial Occurrence of Pulmonary Embolism after Intravenous, Adipose Tissue-Derived Stem Cell Therapy - Jung, Jae Woo; Kwon, Minsuk; Choi, Jae Chol; Shin, Jong Wook; Park, In Won; Choi, Byoung Whui; Kim, Jae Yeol (Yonsei medical journal, 2013)
The therapeutic potential of human multipotent mesenchymal stromal cells, especially human adipose tissue-derived stem cells (hASC), is promising. However, there are concerns about the safety of infusion of hASC in human. Recently, we have experienced pulmonary embolism and infarct among family members who have taken multiple infusions of intravenous autologous hASC therapy. A 41-year-old man presented with chest pain for one month. Chest CT showed multiple pulmonary artery embolism and infarct at right lung. Serum D-dimer was 0.8 μg/mL (normal; 0-0.5 μg/mL). He had received intravenous autologous adipose tissue-derived stem cell therapy for cervical herniated intervertebral disc three times (one, two, and three months prior to the visit). His parents also received the same therapy five times and their chest CT also showed multiple pulmonary embolism. These cases represent artificial pulmonary embolisms and infarct after IV injection of hASC. Follow-up chest CT showed spontaneous resolution of lesions in all three patients.